Faktor Pemilihan Skema Kerjasama Pemerintah dan Badan Usaha dalam Pendanaan Proyek Infrastruktur - Maharani, Dwi Jenita; Maulani, Febiana (Jurnal Bangunan, Konstruksi & Desain, 2024)
To pursue the target of economic growth and development in Indonesia, appropriate infrastructure development is needed so that cooperation between the government and business entities is needed to carry out the development. To carry out cooperation, several factors are needed that are in accordance with the conditions of the project, so that there are no losses for either the investor or the government. One alternative in funding infrastructure is to use the Government and Business Entity Cooperation (KPBU) scheme, so that business entities can participate in providing infrastructure through cooperation agreements. The use of Government and Business Entity Cooperation is one solution in paying for today's infrastructure, so that investors are needed to provide infrastructure using several payment mechanisms in accordance with the agreement between the two parties. Factors that influence the selection of a cooperation scheme are seen from the infrastructure funding factor and the cooperation scheme selection factor. The infrastructure funding factor is seen from the funding pattern, policy framework and return on investment. The scheme selection factor is seen from the aspect of the nature and form of cooperation that occurs, the dimension of the concession time, the scope of work, the aspect of payment, risk and allocation, and the results of the project.